Uncertainty and the Demand for Education - Kodde, David A. (The Review of Economics and Statistics, 1986)
The impact of uncertainty in future income on the demand for education from both theoretical and empirical points of view is analyzed. Theoretical results deviate substantially from their counterparts in models of human capital formation with certain future income. The theory is tested with a sample of high school graduates that contains data on subjective expectations. Empirical evidence from binomial logit analysis does not entirely support the behavioral implications of the theoretical model.